THE RELATIONSHIP BETWEEN ANXIETY LEVEL AND SLEEP QUALITY IN STIKES PANTI RAPIH YOGYAKARTA - Margareta Vinita Sari; Arimbi Karunia; Herlin Lidya (rifascholarpublisher.com, 2024)
Background: Coping mechanisms can affect anxiety levels in college students. High levels of anxiety when dealing with stressors can have an impact on sleep quality student. The results of the preliminary study obtained data that 72% of STIKES Panti Rapih students experienced anxiety and subjectively, 53.5% of college students rated their sleep quality as poor. Therefore, this is important to research, besides that similar research has never been studied at STIKes Panti Rapih Yogyakarta. Objective: this study aims to determine the relationship between anxiety levels and sleep quality in STIKes Panti Rapih Yogyakarta students. This research method uses descriptive analytics with cross-sectional analytical approach. Sampling techniques used is a random sampling cluster, with a sample of 272 students. Data collection methods conducted using ZSAS anxiety questionnaires and PSQI sleep quality. Result: The characteristics of respondents are female (85.3%) and male (14.7%), respondents aged 17-25 years (88.6%), 26-35 years (7.7%), 36-45 years (2.9%), 45-55 years old (0.4%), 56-65 years old (0.4%), and respondents from the S1 Nursing study program (38.2%), D3 Nursing (15.4%), S1 Nutrition (19.1%), Nursing Profession (19.1%), RPL Program (7.4%), and program Transfer (0.7%). The picture of the level of anxiety in students is not anxious, namely (46.7%), students with mild anxiety (38.2%), students with moderate anxiety 11.4%, and Students with severe anxiety (3.7%), then for an overview of sleep quality on Students with poor sleep quality (63.6%) and good sleep quality (36.4%). There was a significant relationship between anxiety levels and the quality of student sleep STIKes Panti rapih Yogyakarta with p value 0.000. Tip: Expected For related institutions, they can provide counseling guidance facilities for students who experiencing anxiety in addition to going through an academic advisor.